Hilirisasi Sistem Pengendalian Air Conditioner (AC) Berbasis IoT melalui Implementasi di Masjid Baitussyukur - Rohmah, Ratnasari Nur; Purwoto, Bambang Hari; Huda, Taufiq Nur; Ismi Dina Solikha (LOSARI DIGITAL, 2026)
The Baitussyukur Mosque encountered operational challenges in managing its air conditioning (AC) system due to manual operation that depended on the physical presence of a caretaker, affecting worshippers’ comfort and reducing energy efficiency. This community service program aimed to implement an Internet of Things (IoT)-based AC control system to improve operational efficiency and enhance worshippers’ comfort. The program applied a NodeMCU ESP8266-based IoT control system integrated with an infrared module and connected to the Blynk platform, enabling real-time, remote, and automatic AC operation according to the five daily prayer schedules (activated 10 minutes before prayer and deactivated 10 minutes after prayer). The activities were conducted in three stages: preparation, installation and training, and evaluation. Evaluation was carried out using a structured questionnaire consisting of 15 items on a 4-point Likert scale. The results showed an average score of 3.93 out of 4.00, indicating a very high level of success and positive impact. The implementation significantly improved operational efficiency, reduced dependency on manual operation, and increased the technical capacity of mosque administrators in managing technology-based public facilities.